Transient Treg‐cell depletion in adult mice results in persistent self‐reactive CD4+ T‐cell responses. Issue 12 (2nd November 2014) - Nyström, Sofia N.; Bourges, Dorothée; Garry, Sarah; Ross, Ellen M.; van Driel, Ian R.; Gleeson, Paul A.
Abstract : Depletion of Foxp3 + CD4 + regulatory T cells (Treg) in adults results in chronic inflammation and autoimmune disease. However, the impact of transient Treg‐cell depletion on self‐reactive responses is poorly defined. Here, we studied the effect of transient depletion of Treg cells on CD4 + T‐cell responses to endogenous self‐antigens. Short‐term ablation of Treg cells in mice resulted in rapid activation of CD4 + T cells, increased percentage of IFN‐γ + and Th17 cells in lymphoid organs, and development of autoimmune gastritis. To track self‐reactive responses, we analyzed the activation of naïve gastric‐specific CD4 + T cells. There was a dramatic increase in proliferation and acquisition of effector function of gastric‐specific T cells in the stomach draining LNs of Treg‐cell‐depleted mice, compared with untreated mice, either during Treg‐cell depletion or after Treg‐cell reconstitution. Moreover, the hyperproliferation of gastric‐specific T cells in the Treg‐cell‐ablated mice was predominantly antigen‐dependent. Transient depletion of Treg cells resulted in a shift in the ratio of peripheral:thymic Treg cells in the reemerged Treg‐cell population, indicating an altered composition of Treg cells. These findings indicate that transient Treg‐cell depletion results in ongoing antigen‐driven self‐reactive T‐cell responses and emphasize the continual requirement for an intact Treg‐cell population.